Analisis Penerapan Sistem Manajemen K3 (Smk3) di Perusahaan Migas Indonesia - Shabina Aulia; Susilawati Susilawati (PT. Alahyan Publisher Sukabumi, 2024)
The oil and gas industry plays a very important role in efforts to meet the needs of the world community in this modern era. In Indonesia, the oil and gas industry, or what we often know as the OIL and Gas industry has developed very rapidly. Jobs in the oil and gas industry sector have very high potential for danger and risk. Based on data collected by BPJS Employment throughout 2020 to 2022, the number of work accidents tends to increase, this also includes data related to Occupational Diseases (PAK). The aim of carrying out this research is to find out how the K3 Management System (SMK3) is implemented by companies in the Indonesian Oil and Gas Industry. This research uses the literature study method. The research results found that the SMK3 implemented by companies in the oil and gas industry sector in Indonesia was running well and optimally. The majority of companies in the oil and gas sector in Indonesia have a high commitment to K3 in their work environment.